The Role of the Great Arts and Literature in Narrative Counselling to Reveal Beauty as a Life-Giving Healing Experience and a Rediscovery of the Human Spirit as a Noetic Spirit - Meylahn, Johann-Albrecht (University of Pretoria, 2020)
Dissertation (MTheology)--University of Pretoria, 2019.